Polymethoxylated Flavones from Orange Peels Inhibit Cell Proliferation in a 3D Cell Model of Human Colorectal Cancer. - Silva, Inês; Estrada, Marta F.; V. Pereira, Carolina; da Silva, Andreia Bento; Bronze, Maria R.; Alves, Paula M.; Duarte, Catarina M.M.; Brito, Catarina; Serra, Ana Teresa (Nutrition & Cancer)
Polymethoxylated flavones (PMFs) have been recognized to inhibit colorectal cancer proliferation through various mechanisms, however most of these studies have been performed on cells grown as monolayers that present limitations in mimicking the 3D tumor architecture and microenvironment. The main aim of this study was to investigate the anticancer potential of an orange peel extract (OPE) enriched in PMFs in a 3D cell model of colorectal cancer. The OPE was developed by supercritical fluid extraction and the anticancer effect was evaluated in HT29 spheroids cultures in a stirred-tank based system. Results showed that OPE inhibited cell proliferation, induced cell cycle arrest (G2/M phase), promoted apoptosis, and reduced ALDH+population on HT29 spheroids. The antiproliferative activity was significantly lower than that obtained for 2D model (EC50 value of 0.43 ± 0.02 mg/mL) and this effect was dependent on diameter and cell composition/phenotype of spheroids derived from different culture days (day 3 – 0.53 ± 0.05 mg/mL; day 5 – 0.55 ± 0.03 mg/mL; day 7 – 1.24 ± 0.15 mg/mL). HT29 spheroids collected at day 7 presented typical characteristics ofin vivosolid tumors including a necrotic/apoptotic core, hypoxia regions, presence of cancer stem cells, and a less differentiated invasive front. Nobiletin, sinesentin, and tangeretin were identified as the main compounds responsible for the anticancer activity.